Digitale Öffentlichkeit(en). Linguistische Perspektiven - Merten, Marie-Luis; Knuchel, Daniel (Zeitschrift für germanistische Linguistik, 2024)
In this thematic volume we ask how digitalization and mediatization are transforming public communication and its conceptual understanding. This introductory text delves into the historical shift from oral and body media to written media in societal communication, highlighting the evolution through telecommunication mass media to the replacement of analog communication by digital forms. It addresses the lack of consensus on the definition of ‘publics’ and public communication, underscoring the multidimensional, heterogeneous, and fluid nature of these concepts. We ask how digitalization and mediatization processes raise questions about fundamental changes in publics due to new technological-communicative possibilities. Furthermore, we discuss the concept of publics as communicatively constructed and maintained, shaped by media and community ideologies. We propose a continuum model for digital/digitized publics, ranging from dyadic communication to multi-party communication. It emphasizes four key aspects for linguistic engagement with digital publics: communicative construction, technical and social affordances, multiplicity of addressing, and practices of digital community formation. With this model and the contributions following the introduction we contribute to a nuanced understanding of digital publics, considering their scale, complexity, and the dynamics of content creation and audience interaction.